2017
DOI: 10.1111/ajt.13995
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms and Long-Term Clinical Outcome in Renal Transplant Patients: A Validation Study

Abstract: Genome-wide association studies (GWAS) are designed to investigate single nucleotide polymorphisms (SNPs) and the association with a clinical phenotype. A previous GWAS performed in 300 renal transplant recipients identified two SNPs (rs3811321 and rs6565887) associated with serum creatinine and clinical outcome. We sought to validate these findings. Genotyping of the two SNPs was performed using Taqman assays in 1638 Caucasians participating in the Assessment of LEscol in Renal Transplant (ALERT) study. Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…However, the study did not include a validation cohort. Attempted validation of the significance of these SNPs was performed in a separate Caucasian cohort of 1638 participants from the ALERT study, using the outcomes of death‐censored graft survival or mortality . No association was demonstrated in this study for either endpoint.…”
Section: Allograft Functionmentioning
confidence: 90%
“…However, the study did not include a validation cohort. Attempted validation of the significance of these SNPs was performed in a separate Caucasian cohort of 1638 participants from the ALERT study, using the outcomes of death‐censored graft survival or mortality . No association was demonstrated in this study for either endpoint.…”
Section: Allograft Functionmentioning
confidence: 90%
“…In an attempt to validate results of an earlier GWAS reporting two variants associated with death-censored graft survival, Pihlstrøm was unable to find a significant association with either variant. 10 In the latest GWAS reported by Ghisdal et al, using a DNA pooling approach, rs10765602 in the CCDC67 gene and rs7976329 in the PTPRO gene, associated with AR, were significant in both a discovery and a validation cohort but have not yet been validated by other investigators.…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8] A study from 2013 identified recipient genotype loci on chromosomes 14 and 18 which significantly associated with 5 years serum creatinine and long-term graft survival. 9 This highlights the need for larger, robust GWAS of allograft outcome to determine the extent to which common variation affects the outcome of kidney transplantation. 9 This highlights the need for larger, robust GWAS of allograft outcome to determine the extent to which common variation affects the outcome of kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%